2011
DOI: 10.1021/la203738h
|View full text |Cite
|
Sign up to set email alerts
|

Organic Modification and Subsequent Biofunctionalization of Porous Anodic Alumina Using Terminal Alkynes

Abstract: Porous anodic alumina (PAA) is a well-defined material that has found many applications. The range of applications toward sensing and recognition can be greatly expanded if the alumina surface is covalently modified with an organic monolayer. Here, we present a new method for the organic modification of PAA based on the reaction of terminal alkynes with the alumina surface. The reaction results in the the formation of a monolayer within several hours at 80 °C and is dependent on both oxygen and light. Characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
0
2

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(60 citation statements)
references
References 92 publications
6
52
0
2
Order By: Relevance
“…This finding is strongly supported by the analogous reaction of 1-alkynes on the η-alumina surface, which also displays surfacebound carbonyl groups. 29 In contrast, alkynes were shown to bind to the silicon carbide surface via a double Markovnikov addition, 19 but that bonding situation yields significantly different spectra.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is strongly supported by the analogous reaction of 1-alkynes on the η-alumina surface, which also displays surfacebound carbonyl groups. 29 In contrast, alkynes were shown to bind to the silicon carbide surface via a double Markovnikov addition, 19 but that bonding situation yields significantly different spectra.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To circumvent such hydrolytic reactivity and to obtain a wider access to surface-modified substrates, our group has recently shown the potential of the modification with 1-alkenes or 1-alkynes of hydroxyl-terminated surfaces such as silica, 28 indium tin oxide (ITO), 3 alumina, 29 and silicon carbide (SiC). 19 On such surfaces, the surface properties (wettability and surface dipole/band bending) can be tuned in great detail via modification of the top group.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accurately benchmarked DFT simulations (based on B3LYP/6‐311G(d,p) level calculation) of C1s XPS spectra,148 showed that a CO signal is to be expected at 289.5 eV, while ‐ C ‐CO carbon atom should give rise to a signal at 287.6 eV, in close to agreement with the experiment. The mechanism for such an oxidation reaction is not fully clear yet, also in view of the heterogeneity of the surface, but such reactions have also been observed for the analogous attachment of 1‐alkynes onto porous aluminum oxide 149. For 1‐alkenes oxidative attachment to yield 1‐carboxylic acids has been observed both on CrN and Al 2 O 3 .…”
Section: Alkenes and Alkynesmentioning
confidence: 97%
“…29 In all cases, upon ambient plasma ionization, either with direct analysis in real time (DART) 28 or with low-temperature plasma (LTP), 29 the desorption of monomeric and dimeric thiolate molecules from the gold surfaces was observed, which is consistent with previous surface MS studies. 9,13,14,17 However, little is known about the fragmentation of monolayers with stronger interfacial bonds tethering the monolayer, that is, covalently bound monolayers on glass, 30 silicon nitride (Si 3 N 4 ), 31 silicon (Si), 32 alumina (Al 2 O 3 ), 33 etc.…”
mentioning
confidence: 99%